2022
DOI: 10.3389/fpsyt.2022.936283
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear association between Mediterranean diet and depressive symptom in U.S. adults: A cross-sectional study

Abstract: The Mediterranean diet (MED), a dietary pattern rich in fruits and vegetables, whole grains, legumes, nuts, fish, and olive oil, has anti-oxidative and anti-inflammatory effects. Although some data suggest that MED adherence is associated with decreased manifestation of depressive symptoms, it remains necessary to further analyze this apparent non-linear association as well as the influence of different factors on the relationship between MED and depression. Here, we investigated associations between the alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Previous studies have demonstrated that both diets reduce PD risk [ 13 , 14 , 15 , 18 , 25 , 26 ] or delay the onset of motor symptoms [ 14 , 25 , 26 ]. In previous studies, the MEDI diet has been associated with improved NMS of constipation and indigestion [ 38 ], cognitive impairment [ 39 ], and depression [ 40 , 41 , 42 ] in PwPD. A higher MIND diet score was substantially associated with slower cognitive decline with aging in the MAP Study [ 17 ], and improved verbal memory scores in a population-based study of American women [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that both diets reduce PD risk [ 13 , 14 , 15 , 18 , 25 , 26 ] or delay the onset of motor symptoms [ 14 , 25 , 26 ]. In previous studies, the MEDI diet has been associated with improved NMS of constipation and indigestion [ 38 ], cognitive impairment [ 39 ], and depression [ 40 , 41 , 42 ] in PwPD. A higher MIND diet score was substantially associated with slower cognitive decline with aging in the MAP Study [ 17 ], and improved verbal memory scores in a population-based study of American women [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…MedDiet is a measure indicator of adherence to the Mediterranean dietary pattern [ 18 ]. In this study, MedDiet contains eight components: vegetables, fruits, nuts, whole grains, legumes, red and processed meats, fish and olive oil.…”
Section: Methodsmentioning
confidence: 99%
“…Adherence to the MED was calculated by two steps. First, 24-h dietary recall data was linked to United States Department of Agriculture, Food Patterns Equivalents Database to convert different foods, beverages into equal amounts of food pattern components [ 31 ]. In the second step, the alternative MED (aMED) index was used to assess the adherence to the MED [ 32 ].…”
Section: Methodsmentioning
confidence: 99%